Three-dimensional architecture of the ligamentum teres in the human hip joint - Kaku, Nobuhiro (Muscles Ligaments Tendons J, 2018)
BACKGROUND: We aimed to investigate the three-dimensional structure of the collagenous fibers of the ligamentum teres (LT) of the human hip and clarify the LT micro-anatomy at the attachment of the femoral head. METHODS: Femoral heads and LT were collected during hip arthroplasty. Specimens were cut into 5–10-mm squares, prepared, developed, and observed under a light microscope. Next, specimens were prepared and examined under a scanning electron microscope (SEM). RESULTS: Under optical microscope, LT adhered to the artificial cartilage at the attachment of the femoral head. Under SEM, LT comprised parallelly arranged collagenous fibers and the fine collagenous fibrils were twisted. While the central collagenous fibers of the LT at the attachment of the femoral head penetrated the articular cartilage tissue and reached the ring-shaped bone, fibers at the margin traversed and adhered to the cartilage surface. CONCLUSION: Articular cartilage and subchondral bone are present at the LT attachment to the femoral head. Although collagenous fibers of the LT show parallel arrangement at the main trunk, they are dispersed at the cartilage surface and not all reach the thin subchondral bone of the femoral head. This could possibly weaken ligament strength at the attachment of the femoral head. LEVEL OF EVIDENCE: IV.